ASSOCIATION OF INTELLECTUAL DEFICIT, ENDOCRINE-METABOLIC DISORDERS AND DISORDERS OF MORPHOGENESIS AND TOOTH ERUPTION: CASE REPORT - Da Silva Dias Cuppari, Adriana; Nelo Pedreira, Erick; Cavaleiro, Rosely; Souto El Husny, Antonette (Health and Society, 2022)
Objective: Report of a clinical case of Hypoparathyroidism (HPP) treated at the Dental Clinic of the Specialization of Patients with Special Needs (PNE) of the Federal University of Pará (UFPA). Methods: Information was obtained through reports provided by the mother, clinical evaluation with the patient, oral photographic records, Cone Beam Computed Tomography (CBCT), X-Ray and Skull Tomography, Carpal Rx, Pelvic Rx, blood tests, ultrasound of the kidneys, evaluation with an ophthalmologist. Hypoparathyroidism is a disease that occurs when the PTH (parathyroid hormone) hormone that is produced by the parathyroid glands does not work or is no longer produced. Conclusion: The result of the lack of this hormone is a drop in blood calcium levels, and an increase in alkaline phosphatase causing various symptoms. Acquired (something that develops in childhood or adulthood). The cause can be acquired, transient, congenital, inherited or pseudohypoparathyroidism.